Religious Approaches on Work Ethics: An Alternative Islamic Model - Haj Ali, Ahmed Raja; Achour, Meguellati; Noordin, Kamaruzaman (Online Journal of Research in Islamic Studies, 2019)
A longstanding debate has been whether religion plays a role in workplace values. Most religions have an ethical component. In recent years an increasing presence of religious approaches, in both empirical and conceptual research, can be noted, in spite of some objections to the presence of religions in the work ethics field. Empirical research, generally based on psychological and sociological studies, shows the influence of religious faith on several work issues. Conceptual research includes a variety of work ethics issues studied from the perspectives of different religions and wisdom traditions such as Judaism, Buddhism, Christianity, and Islam. Ethics, which is a major branch of philosophy, encompasses right conduct and good life. It is significantly broader than the common conception of analyzing right and wrong. Islamic work ethic is a modern multidimensional construct, linking organizational prosperity and social welfare, therefore, the current research seeks to strengthen the role of IWE, expand the understanding of its dimensions.